An analysis of pesticide use in rice production in the Red River Delta, Vietnam : a case study in Dan Phuong district, Hatay province - Do Thanh Lam; Upasena, Selawa H.; Boonjit Titapiwatanakun; Johnsen, Steffen; The Thai King's Scholarship (Bangkok : Asian Institute of Technology, 1995)
Rice has been so far the most dominant crop in Vietnam agricultural production in general and in the Red River Delta crop production system in particular. Food deficit problem due to high population growing pressure within limited agricultural land as in the RRD has been the leading force to rice intensification. In order to meet the country's food requirement and to make Vietnam self-sufficient, the Government has put rice production under the first priority to be intensified. Short duration high yielding varieties together with high input investment such as chemical fertilizers and pesticides, are the main components to rice intensification. However, indiscriminate use of pesticides has led to serious agronomic and environmental problems. The common brown plant hopper resurgence in both two rice growing regions of the country, pests resistance to pesticides, occurrence of new rice diseases such as bacterial grain rot and leaf yellowing, are said to be induced by pesticide use. In this study, results from farm survey have revealed that Methyl-parathion (Wofatox, Methaphos) and Methamidophos (Monitor) are the most dominant insecticides used by farmers in area studied, Dan Phuong district, whereas Validamycin A is the most prevalent fungicide used. These two insecticides are classified by WHO as the extremely (Ia) and highly hazardous products (lb) respectively, and their long term use may lead to farmers' health and environmental problems. Analyzing the plant protection system in Vietnam, as well as Government pesticide policies has allowed to understand that pesticide subsidies in the form of hidden subsidies (no import tax) and direct subsidies (State pesticide reserve and price support) have indeliberately encouraged farmers to use pesticides because of low price. Altogether, the poor pesticide management in terms of quality control/inspection, policies in extension and commercial companies have been the main reasons to explain for the present pesticide usage by farmers. Pesticide analysis at farm level has confirmed the impact of different types of pest management towards farmers' pesticide use. Under the context of non-IPM training, the contract system of pest management has led farmers to over use pesticide, whereas the open system has led farmers to general less pesticide use. However, without IPM training farmers in the open system may over use again as in the case of contract system. Results from the survey has suggested the important need to train to either farmers, plant protection team members, traders and extension workers. Farm income situation has shown significant effects on farmers' pesticide practices. The high income farmers with sufficient labor and capital tend to spray more than low income farmers. However, once they are IPM farmers this attitude may be changed towards more cost-effective and environmentally friendly rice production system. Then, IPM training with participatory approach appears to be promising in the coming years to reduce pesticide use. However, full cooperation from Government and local authorities in setting up proper policies and supports are important issues need to be addressed.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Science, School of Environment, Resources, and Development
Thesis (M.Sc.) - Asian Institute of Technology, 1995
Keywords: Pesticides -- Vietnam -- Hatay; Rice -- Vietnam -- Red River Delta